2021
DOI: 10.1016/j.jcyt.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell variables influencing clinical potency: the impact of viability, fitness, route of administration and host predisposition

Abstract: The International Society for Cell & Gene Therapy mesenchymal stromal cell (MSC) committee has been an interested observer of community interests in all matters related to MSC identity, mechanism of action, potency assessment and etymology, and it has regularly contributed to this conversation through a series of MSC pre-conferences and committee publications dealing with these matters. Arising from these reflections, the authors propose that an overlooked and potentially disruptive perspective is the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 75 publications
1
45
0
Order By: Relevance
“…It encompasses four mechanisms by which derivatives of MSCs can retain significant clinical efficacy, including apoptosis, autophagy, mitochondrial transfer, and extracellular vesicle production [57]. The bioactive parts of dead or dying MSCs can trigger immunomodulatory properties in the host without the concern over cell survival and the formation of large aggregates [58][59][60].…”
Section: Necrobiologymentioning
confidence: 99%
“…It encompasses four mechanisms by which derivatives of MSCs can retain significant clinical efficacy, including apoptosis, autophagy, mitochondrial transfer, and extracellular vesicle production [57]. The bioactive parts of dead or dying MSCs can trigger immunomodulatory properties in the host without the concern over cell survival and the formation of large aggregates [58][59][60].…”
Section: Necrobiologymentioning
confidence: 99%
“…In response to inflammatory stimuli, live MSCs are capable of releasing an active secretome that consists of potent agents for immunomodulation, as opposed to dead or non-viable MSCs that fail to inhibit immune cell function [ 34 ]. MSC potency can be assessedlargely by cell viability, one of the most important cellular attributes influencing persistent therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy revolves around the use of banked products, with studies demonstrating reduced therapeutic potential, loss of functionality and increased susceptibility to trigger prothrombotic events (177)(178)(179)(180)(181), while others have showed minimal impairment of cell viability and fitness (182,183). In this context, clinical potency has been linked with the concept of metabolic fitness and product viability at the time of infusion (184,185) making it critical to develop manufacturing methods to rescue cryopreserved cells and restore cell functionality (186). Intriguingly, other studies have demonstrated that apoptotic or dead MSCs, and therefore less metabolically active, confer therapeutic benefits by enhancing the host innate immune response (187)(188)(189).…”
Section: Clinical Translation Of Msc Therapies In Kidney Diseasementioning
confidence: 99%
“…Determining novel predictive biomarkers of therapeutic potency is of utmost importance before clinical usage, and viability and metabolic fitness have been recently proposed as potency qualities (184). Metabolic status is affected after longterm in vitro expansion, and it can reflect differential stemness behavior (242,(247)(248)(249), as well as cell immune functionality (250).…”
Section: Growth Kineticsmentioning
confidence: 99%